2023
DOI: 10.1210/clinem/dgad173
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Predictive Factors of Outcome in Medullary Thyroid Microcarcinoma

Abstract: Purpose Management of sporadic medullary thyroid microcarcinoma smaller than 1 cm (micro-MTC) is controversial due to conflicting reports of prognosis. As these cancers are often diagnosed incidentally, they pose a management challenge when deciding on further treatment and follow-up. Methods Micro-MTCs were identified from a prospectively maintained surgery database and slides were reviewed to determine pathological grade. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Machens et al [ 21 ] studied 233 patients with MTMC and found that lymph node metastases were common. In a recent study, Kesby et al [ 22 ] studied 42 patients with MTMC, of which five (12%) had lymph node metastases; during a median follow-up of 6.6 years, five (12%) had recurrence, and three (7%) died. In summary, studies of MTMC have led to very different conclusions from those of papillary thyroid microcarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Machens et al [ 21 ] studied 233 patients with MTMC and found that lymph node metastases were common. In a recent study, Kesby et al [ 22 ] studied 42 patients with MTMC, of which five (12%) had lymph node metastases; during a median follow-up of 6.6 years, five (12%) had recurrence, and three (7%) died. In summary, studies of MTMC have led to very different conclusions from those of papillary thyroid microcarcinoma.…”
Section: Discussionmentioning
confidence: 99%